Pengaruh Kecerdasan Emosional dan Minat Belajar terhadap Hasil Belajar Biologi Siswa Kelas X MIPA di SMAN Rambipuji Jember - Novia Miftahul Janah; Umi Farihah (HMPS Tadris Biologi FTIK IAIN Jember, 2021)
This research is motivated by students as components that have the responsibility to improve the quality of education. Positive changes in student behavior which are the result of the learning process at school can be seen from their result of learning. Student learning results can be seen from the cognitive, affective and psychomotor factors of students wherein learning is not only mastery the theory concepts of subject, but also mastery of habits, perceptions, pleasures, interests and talents, social adjustment, skills, goals, desires and expectations. One of the psychological factors that influence learning results that are considered the most essential are intelligence, and interest. This study were aimed to determine the effect of emotional intelligence and interest in learning simultaneously and partially on the biology learning results of class X MIPA students at SMAN RambiPuji Jember. This study was used a quantitative approach with the type of associative research conducted at SMAN RambiPuji Jember. The population includes all students of class X, 143 students were taken. Determination of the number of sample were used the Slovin formula obtained 105 students, using the cluster random sampling technique, three classes were taken, totaling 107 students. Data collection techniques were used questionnaires and documentation and data analysis were used multiple linear regression analysis. The results showed that there was a simultaneous and partial influence of emotional intelligence and interest in learning on the biology learning outcomes of students of class X MIPA at SMAN Rambi Puji Jember. This research is motivated by students as components that have the responsibility to improve the quality of education. Positive changes in student behavior which are the result of the learning process at school can be seen from their result of learning. Student learning results can be seen from the cognitive, affective and psychomotor factors of students wherein learning is not only mastery the theory concepts of subject, but also mastery of habits, perceptions, pleasures, interests and talents, social adjustment, skills, goals, desires and expectations. One of the psychological factors that influence learning results that are considered the most essential are intelligence, and interest. This study were aimed to determine the effect of emotional intelligence and interest in learning simultaneously and partially on the biology learning results of class X MIPA students at SMAN RambiPuji Jember. This study was used a quantitative approach with the type of associative research conducted at SMAN RambiPuji Jember. The population includes all students of class X, 143 students were taken. Determination of the number of sample were used the Slovin formula obtained 105 students, using the cluster random sampling technique, three classes were taken, totaling 107 students. Data collection techniques were used questionnaires and documentation and data analysis were used multiple linear regression analysis. The results showed that there was a simultaneous and partial influence of emotional intelligence and interest in learning on the biology learning outcomes of students of class X MIPA at SMAN Rambi Puji Jember. Keywords: emotional intelligence, interest in learning, learning outcomes Penelitian ini dilatarbelakangi oleh siswa sebagai komponen yang mempunyai tanggung jawab untuk meningkatakan kualitas pendidikan. Perubahan positif perilaku siswa yang merupakan hasil dari proses belajar di sekolah dapat dilihat dari hasil belajarnya. Hasil belajar siswa dapat dilihat dari aspek kognitif, afektif dan psikomotorik siswa karena belajar tidak hanya penguasaan konsep teori mata pelajaran saja, tetapi juga penguasaan kebiasaan, persepsi, kesenangan, minat-bakat, penyesuaian sosial, keterampilan, cita-cita, keinginan dan harapan. Salah satu faktor psikologis yang mempengaruhi hasil belajar yang dipandang paling esensial adalah kecerdasan, dan minat. Penelitian ini bertujuan untuk mengetahui pengaruh kecerdasan emosional dan minat belajar secara simultan dan parsial terhadap hasil belajar biologi siswa kelas X MIPA di SMAN Rambipuji Jember. Penelitian ini menggunakan pendekatan kuantitatif dengan jenis penelitian asosiatif yang dilakukan di SMAN Rambipuji Jember. Populasi meliputi seluruh siswa kelas X yang berjumlah 143 siswa. Penentuan jumlah sampel menggunakan rumus slovin yang didapat 105 siswa, dengan menggunakan teknik cluter random sampling maka diambil sebanyak tiga kelas yang berjumlah 107 siswa. Teknik pengumpulan data menggunakan angket dan dokumentasi serta analisis data menggunakan analisis regresi linier berganda. Hasil penelitian menunjukkan bahwa terdapat pengaruh kecerdasan emosional dan minat belajar secara simultan dan parsial terhadap hasil belajar biologi siswa kelas X MIPA di SMAN Rambipuji Jember. Kata kunci: kecerdasan emosional, minat belajar, hasil belajar